STUDI KASUS IMBANGAN ANGKUTAN SEDIMEN DI KALI KRASAK - Darmono, Lanaria Pangestu (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
This study aims to find out the volume of a flood plan and balance between sediment raised in the mining of sand and sediment that comes in the time of flooding in kali Krasak river’s area regional of Kuwu’an.The method of study is using observation method, interview method, and literature method. Hydrology data used in this study is map kali Putih river, map rain stasiun, and gradation of sand grains. To calculate the volume of a flood plan is using the rational method, weduwen method, and hasper method. And to calculate sediment transport using Mayer, Peter and Muller formulation.The calculation based on four rains station Kalibawang, Kemput, Plunyon, Babadan station using (1) Rasional, (2) Weduwen and (3) Hasper to five years reissue period are (1) 418,68 m3/second, (2) 145,08 m3/second and (3) 58,90 m3/second. The result of the calculation of sediment transport using Meyer, Petter and Muller formulation produces sediment transport base for the entire widht of the river of 4,16 m3/second, and base sediment transport for one hour of 14.962 m3. The study result show that the mining sediment of Kuwu’an area is 172.800 m3/year. So the mining was done in Kuwu’an for one year is 172.800 m3 can be offset by during floods for 11,54 hours resulting heaps of 172.823 m3. Keywords: Balance river Krasak, flood plan, sediment transport